A Simple Proof of Ergodic Theorem for Recursive Decision (London Journal of Research In Management & Business, 2025)
This paper show that rational choice on recursive decision under measure preserving transformation can lead to asymptotic behavior in a stationary environment, and providing sufficient conditions for recursive decision systems to possess ergodic properties from its stationary mean.
Keywords: Machine learning; Volatility; Pairs Trading; Clustering Algorithms; cryptocurrencies market; cointegration; algorithmic trading; trading strategies; market efficiency.; managerial overconfidence; cash holdings; internal control JEL: G30; G40; management; leadership; different; Similar; Complementary; Recursive Decision; Ergodicty; Complex Dynamics; Stationary Equilibria.